Understanding the Concept of Gender in Qur'anic Interpretation (A Feminist Study of the Thought of M. Quraish Shihab) - Anwar, Akhmad Khoirul; Ghianovan, Jaka; Shofa, Ida Kurnia (Jurnal Semiotika-Q: Kajian Ilmu al-Quran dan Tafsir, 2024)
In an increasingly developing global context, the role and rights of women in efforts to improve the economy and welfare of society are increasingly becoming a hot topic of discussion. This shows the importance of exploring Islam’s contri-bution to the struggle for gender equality and contributing to the global discourse on women's rights. This article aims to understand the concept of gender from the perspective of Tafsir al-Mishbah. The method used is qualitative with a type of library research by collecting, analyzing and synthesizing Al-Qur'an texts   that discuss the concept of gender. By using an Ijmali tafsir approach that reveals  a concise and global interpretation, this article shows that Islam affirms the essential equality between men and women before Allah, despite biological differences. M. Quraish Shihab's thoughts emphasize that these differences are nature that has been established by Allah, but are not a reason to demean or ignore women's rights. This indicates the importance of fighting for gender equality in the current context and encouraging an inclusive and fair understanding of the role of women in society.